Susceptibility of myotis lucifugus to heterologous and homologous rabies viruses (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies virus (RV) maintenance in bats is not well understood. Eptesicus fuscus, Myotis lucifugus, and Tadarida brasiliensis are the most common bats species in the US. These colonial bat species also have the most frequent contact with humans and domestic animals. However, the Lasionycteris noctivagans/ Perimyotis subflavus (Ln/Ps) RV is associated with the majority of human rabies virus infections in the United States and Canada. This is of interest because the L. noctivagans and P. subflavus bat species are more solitary bats with less frequent human interaction. Our interest was to determine the likelihood of a colonial bat species becoming infected with and transmitting a heterologous RV. To determine the potential of heterologous RV infection in colonial bat species, M. lucifugus bats were inoculated with a homologous or one of two heterologous (E. fuscus and L. noctivagans) RV. Additionally, to determine if the route of exposure influenced the disease process, bats were inoculated either intramuscularly (i.m.) or subcutaneously (s.c.) with a homologous or heterologous RV. Bats were observed for 6 months. Survivors were challenged i.m. with a homologous RV and observed for an additional 6 months. Our results demonstrate intramuscular inoculation results in a more rapid progression of disease onset as compared to a significantly longer incubation time in bats inoculated s.c. Additionally, cross protection was not consistently achieved in bats previously inoculated with a heterologous RV following a six month challenge with a homologous RV. Finally, bats that developed rabies following s.c. inoculation were significantly more likely to shed virus in their saliva and demonstrated increased viral tissue tropism. In summary, bats inoculated via the s.c. route are more likely to shed virus thus increasing the potential for transmission.